Qualitative phytochemical screening of indian witchweed: Striga asiatica (L.) O. Ktze - an unexplored medicinal parasitic plant - R, Kakpure M; P, Rothe S (Journal of Experimental Sciences, 2012)
Many herbal remedies have been employed in various medical systems for the treatment of different diseases. The parasitic plant Striga asiatica (L.) O. Ktze commonly known as witch weed belongs to family Scrophulariaceae has been used in different system of traditional medicine for curing various diseases and ailments of human beings. The present study deals with the qualitative phytochemical screening of Striga asiatica (L.) O. Ktze of whole plant powder in six different extracts (i.e. petroleum ether, benzene, chloroform, acetone, ethanol and water). The extracts showed the prominently presence of phytoconstituents like carbohydrates, cardiac glycosides, alkaloids, flavonoids, tannin, phenolics, steroids, coumarins and saponin. However anthroquinone glycosides and quinone are totally absent in all extracts. Most of the phytoconstituents from Striga asiatica (L.) O. Ktze lacks the reports of pharmacological activities, which support its further pharmacological studies.